An enzyme-free, ultrasensitive strategy for simultaneous screening of the p-nitrophenyl substituent organophosphorus pesticides. (15th May 2023) - Sun, Pengyuan; Li, Bingru; Zhen, Jianhui; Zhao, Jie; Jia, Wenshen; Pan, Ligang; Gong, Wenwen; Liang, Gang
Highlights: NaOH instead of hydrolase/nanozyme was applied for the NSOPs hydrolysis. Efficient hydrolysis of the NSOPs was achieved (>96.0 %). Single and/or multiple detection of the NSOPs were realized. The NSOPs were indirectly, sensitively detected with LOD lower than 0.1 ppb. Abstract: An enzyme-free, sensitive, and convenient approach was reported for the P-nitrophenyl substituent organophosphorus pesticides (NSOPs) of paraoxon-methyl (PM), paraoxon-ethyl (PE), parathion-methyl (PTM) and parathion-ethyl (PTE)) by indirectly quantification of the 4-nitrophenol (4-NP, hydrolysis product of the NSOPs). NaOH instead of hydrolase/nanozyme was applied, and temperature, pH, ultrasound was investigated to improve the NSOPs hydrolysis. Under the optimized conditions, the hydrolysis efficiencies were up to 99.9 %, 99.9 %, 99.6 %, 96.0 % for PM (10 min), PE (30 min), PTM (90 min) and PTE (120 min), based on which a low detection limits of 0.06 (PM), 0.07 (PE), 0.06 (PTM) and 0.07 (PTE) ppb were calculated with the 4-NP detection limit (0.03 ppb). Furthermore, the method exhibited good performance for the NSOPs with recoveries from 88.87 % to 100.33 % in real samples. This indirect approach offered an ultrasensitive alternative for the NSOPs detection, which holds great potential in practical application for the assessment of food safety and environmental risks.